2006
DOI: 10.1074/jbc.m603484200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 Induces 15-Lipoxygenase-1 Expression in Human Orbital Fibroblasts from Patients with Graves Disease

Abstract: Orbital fibroblasts orchestrate tissue remodeling in Graves disease, at least in part, because they exhibit exaggerated responses to proinflammatory cytokines. A hallmark of late stage orbital disease is visionthreatening fibrosis, the molecular basis of which remains uncertain. We report here that the Th2 cytokines, interleukin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 55 publications
2
28
0
2
Order By: Relevance
“…These results suggest that the induction of activity was not accompanied by a change in the steady state levels of protein. These observations are in agree- ment with interleukin-4 induction of 15-LOX-1 expression in fibroblasts that starts 16 h after cytokine treatment (31). Although it is unclear what mechanisms involved in oxidative stress induce changes 15-LOX-1 activity, the polycystin/lipoxygenase/␣-toxin domain present in lipoxygenases may play a role in this induction (32) and in a possible translocation to the membrane (29).…”
Section: Discussionsupporting
confidence: 76%
“…These results suggest that the induction of activity was not accompanied by a change in the steady state levels of protein. These observations are in agree- ment with interleukin-4 induction of 15-LOX-1 expression in fibroblasts that starts 16 h after cytokine treatment (31). Although it is unclear what mechanisms involved in oxidative stress induce changes 15-LOX-1 activity, the polycystin/lipoxygenase/␣-toxin domain present in lipoxygenases may play a role in this induction (32) and in a possible translocation to the membrane (29).…”
Section: Discussionsupporting
confidence: 76%
“…In agreement with previous results, [2][3][4]7,8,35,36 microarray analysis showed that IL-4 induced a restricted set of genes in human macrophages (204 genes; 0.7% of the transcriptome), 45.6% of which were significantly affected by pretreatment with 10058-F4. Therefore, microarray results indicate that alternative activation genes can be classified as c-MYC dependent (Figure 2) or c-MYC independent (supplemental Figure 1) according to the role of the c-MYC transcription factor in their induction during alternative macrophage activation.…”
Section: C-myc Is Involved In the Expression Of A Distinct Subset Of supporting
confidence: 79%
“…38 Conversely, ALOX15 induction by IL-4 in various cell types, including primary cultures of human monocytes, had been suggested previously to be a STAT6-dependent event. 45,46 Nonetheless, in T-cell lymphoma cells, histone deacetylase inhibitors able to reduce STAT6 and phospho-STAT6 protein expression did not affect ALOX15 expression, 47 suggesting the existence of STAT6-independent intracellular pathways regulating ALOX15 expression in response to IL-4. Similarly, MRC1 induction by IL-4 in macrophages and dendritic cells has been well established.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant differences in cell number were not evident in stained peripheral blood smears, this would not have been sensitive enough to detect functional changes in the leukocytes. Although little information is available about the direct regulation of 15-LO by corticosteroids, the induction of 15-LO-1 expression in vitro by IL-4 and IL-13 can be attenuated by steroids in orbital fibroblasts (47). COX-2 expression was downregulated in all samples from subjects with severe asthma.…”
Section: Discussionmentioning
confidence: 96%